2019
DOI: 10.1111/jsap.13096
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransfusion of canine blood to cats: a review of 49 cases and their outcome

Abstract: Objectives To describe the use of a xenotransfusion protocol, the outcome of xenotransfusion in recipient cats and to assess owner memory of the xenotransfusion. Materials and Methods Cats administered xenotransfusions in two hospitals between January 2016 and July 2018 were included. Adherence to xenotransfusion protocol, cause of anaemia, blood type, packed cell volume (PCV), transfusion volume, transfusion reactions, PCV 12 hours after transfusion and survival to discharge were recorded. Owners of surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(78 citation statements)
references
References 18 publications
(29 reference statements)
4
73
0
Order By: Relevance
“…In a recent retrospective study of 49 canine whole blood to feline transfusion patients, 10 died or were euthanized within 24 h, and a hemolytic transfusion occurred in 63% of the cats (16). That study also identified a febrile non-hemolytic reaction in 12.2% of the cats (16), which was similar to the 10% rate previously reported by another study (20). Azotemia postxenotransfusion is another adverse effect that has been noted in small animal species (5).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In a recent retrospective study of 49 canine whole blood to feline transfusion patients, 10 died or were euthanized within 24 h, and a hemolytic transfusion occurred in 63% of the cats (16). That study also identified a febrile non-hemolytic reaction in 12.2% of the cats (16), which was similar to the 10% rate previously reported by another study (20). Azotemia postxenotransfusion is another adverse effect that has been noted in small animal species (5).…”
Section: Discussionsupporting
confidence: 83%
“…Xenotransfusion has been successfully described in multiple veterinary species for emergency situations (8,(15)(16)(17). Many species differ in blood types and presence of naturally occurring alloantibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of JSAP , Le Gal et al . () report the largest case series of dog‐to‐cat xenotransfusions, confirming previous observations regarding its relative safety. The authors studied the characteristics and outcome of 49 cats that received xenotransfusion with canine blood in two university referral hospitals between January 2016 and July 2018.…”
supporting
confidence: 85%